A Rare Case of Cutaneous Metastasis From Oral Squamous Cell Carcinoma ( OSCC ) and the Possible Role of GALR2 as a Biomarker: A Case Report - Ianny Brum Reis; Milena Moraes de Carvalho; Danilo Paschoal Ferrarezi; Natalie Aparecida Rodrigues Fernandes; Camyla Rodrigues Nascimento; Álvaro Formoso Pelegrini; Aldenora Maria Ximenes Rodrigues; Alex de Freitas Porsani; Flávio Ferlin Arbex; Carlos Rossa Junior (Clinical Case Reports, 2026)
ABSTRACT We report a rare case of cutaneous metastasis from oral squamous cell carcinoma (OSCC). The primary tumor showed low expression of Galanin, CD68, GALR2, and Collagen IV, with increased FOXP3 and Vimentin. Systemic analysis revealed reduced CD8 + cells and increased Tregs. The patient died following aggressive disease progression.